Análise da mobilização, coleta e infusão de células-tronco hematopoiéticas do sangue periférico para transplante autogênico no Hospital Universitário de Santa Maria - Scapin, Valúsia (2013)
The transplantation of hematopoietic peripheral blood stem cells is one of the therapeutic choices for the treatment of various hematological and oncological diseases, extending disease-free survival and, in some cases, providing the cure of the patient. This is a retrospective study in which the medical records of patients who underwent mobilization, collection and infusion of peripheral hematopoietic stem cells for autologous transplantation were analyzed with the objective of evaluating these procedures, identifying the characteristics of the population assisted and verifying the transplant-related mortality and overall survival of transplanted patients. The study analyzes 176 patients (78F/98M) of the Hematology-Oncology Service of the University Hospital of Santa Maria (HUSM) in the period between December 1996 and December 2011. The diagnoses included: Multiple Myeloma (54), Hodgkin Lymphoma (47), Non Hodgkin Lymphoma (35), Acute Myeloid Leukemia (16) and other neoplasias (24) such as Breast Cancer, Wilms Tumor, Ewing s Sarcoma, Neuroblastoma, Amyloidosis, Testicular Tumor, Medulloblastoma, Macroglobulinemia, CNS Tumor. The median age of the patients was 42 years (1 to 69 years). Before the stem cells mobilization, all the patients had already been submitted to some kind of treatment related to the disease and 31% had received previous radiotherapy. The mobilization schema included hematopoietic growth factor (G-CSF) associated our not whit different chemotherapies. The number of mobilization and leukapheresis carried out were 203 and 474 respectively. The desired number of CD34+ cells in the collection was 2,0x106/kg, considering that the majority of patients achieved the quantity expected. The median of total nucleated cells collected was 7,01x108/kg and of CD34+ cells it was of 2,63x106/kg, with a median of two leukapheresis per patient (1 to 6). Of the 176 patients in this study 120 patients were submitted to autologous transplantation, three received two infusions each. The median of total nucleated cells infused was 6,46x108/kg and of CD34+ cells was 3,17x106/kg. After the infusion of hematopoietic stem cells, the recovery of neutrophils occurred between 7 and 28 days (median 10 days), while the platelets between 8 and 79 (median 12 days), considering that three patients did not have platelet recovery. The correlation between the quantity of CD34+ cells infused and the recovery of neutrophils and platelets was verified. Transplantrelated mortality was 5%. The probability of overall survival of the group in a year was of 79,8% and 55,1% in five years. In conclusion, this study demonstrated that the majority of the patients achieved the desired number of CD34+ cells through mobilization and collection and the results obtained with autologous transplantation were similar to those described in the literature.